2022
DOI: 10.1186/s12920-022-01195-y
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of atherosclerotic genes elucidates druggable targets

Abstract: Background Atherosclerosis is one of the major causes of cardiovascular disease. It is characterized by the accumulation of atherosclerotic plaque in arteries under the influence of inflammatory responses, proliferation of smooth muscle cell, accumulation of modified low density lipoprotein. The pathophysiology of atherosclerosis involves the interplay of a number of genes and metabolic pathways. In traditional translation method, only a limited number of genes and pathways can be studied at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…The highest confidence score lies between 0.9 and 1, high confidence score between 0.7 and 0.9, medium confidence score between 0.4 and 0.7 and low confidence score is less than 0.4. In the network, each gene is designated as a node and the interactions between the nodes are designated as edges 46 . The results of the analysis with highest, high, medium and low confidence scores are 7, 8, < 1.11e−16; 7, 14, < 1.0e−16; 7, 20, < 1.0e−16 (nodes, edges, and p value, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The highest confidence score lies between 0.9 and 1, high confidence score between 0.7 and 0.9, medium confidence score between 0.4 and 0.7 and low confidence score is less than 0.4. In the network, each gene is designated as a node and the interactions between the nodes are designated as edges 46 . The results of the analysis with highest, high, medium and low confidence scores are 7, 8, < 1.11e−16; 7, 14, < 1.0e−16; 7, 20, < 1.0e−16 (nodes, edges, and p value, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…ITGB2 is a transmembrane adhesion and signaling receptor expressed only on leukocytes and extracellular vesicles. It promotes an in ammatory reaction and assists leukocytes adhere to tissue and move around [39,40]. Liu et al demonstrated that suppressing the expression of ITGB2 in macrophages in a mouse HF model decreased the in ltration of myocardial immune in ammatory cells and cardiac hypertrophy [41].…”
Section: Discussionmentioning
confidence: 99%
“…ITGB2 is a transmembrane adhesion and signaling receptor expressed only in leukocytes and extracellular vesicles. It promotes an inflammatory reaction and assists leukocytes in adhering to tissues and to move around ( 42 , 43 ). Liu et al.…”
Section: Discussionmentioning
confidence: 99%